MRI cT1–2 rectal cancer staging accuracy: a population‐based study. Issue 10 (16th April 2020) - Detering, R.; van Oostendorp, S. E.; Meyer, V. M.; van Dieren, S.; Bos, A. C. R. K.; Dekker, J. W. T.; Reerink, O.; van Waesberghe, J. H. T. M.; Marijnen, C. A. M.; Moons, L. M. G.; Beets‐Tan, R. G. H.; Hompes, R.; et al.
Abstract : Background: Adequate MRI‐based staging of early rectal cancers is essential for decision‐making in an era of organ‐conserving treatment approaches. The aim of this population‐based study was to determine the accuracy of routine daily MRI staging of early rectal cancer, whether or not combined with endorectal ultrasonography (ERUS). Methods: Patients with cT1–2 rectal cancer who underwent local excision or total mesorectal excision (TME) without downsizing (chemo)radiotherapy between 1 January 2011 and 31 December 2018 were selected from the Dutch ColoRectal Audit. The accuracy of imaging was expressed as sensitivity, specificity, and positive predictive value (PPV) and negative predictive value. Results: Of 7382 registered patients with cT1–2 rectal cancer, 5539 were included (5288 MRI alone, 251 MRI and ERUS; 1059 cT1 and 4480 cT2). Among patients with pT1 tumours, 54·7 per cent (792 of 1448) were overstaged by MRI alone, and 31·0 per cent (36 of 116) by MRI and ERUS. Understaging of pT2 disease occurred in 8·2 per cent (197 of 2388) and 27·9 per cent (31 of 111) respectively. MRI alone overstaged pN0 in 17·3 per cent (570 of 3303) and the PPV for assignment of cN0 category was 76·3 per cent (2733 of 3583). Of 834 patients with pT1 N0 disease, potentially suitable for local excision, tumours in 253 patients (30·3 per cent) were staged correctly as cT1 N0, whereas 484 (58·0 per cent) and 97 (11·6 per cent) were overstaged as cT2 N0 and cT1–2 N1 respectively. Conclusion: This Dutch population‐based analysis of patients who underwent local excision or TME surgery for cT1–2 rectal cancer based on preoperative MRI staging revealed substantial overstaging, indicating the weaknesses of MRI and missed opportunities for organ preservation strategies. Abstract : This population‐based study determined the accuracy of routine daily MRI staging of early rectal cancer, whether or not combined with endorectal ultrasonography. The results showed that preoperative MRI led to substantial overstaging in patients who underwent local excision or total mesorectal incision surgery for cT1–2 rectal cancer, indicating the weaknesses of MRI and missed opportunities for organ preservation strategies. Imaging weakness Abstract : Antecedentes: Una adecuada estadificación mediante resonancia magnética nuclear (RMN) de los cánceres de recto en estadios precoces es esencial para la toma de decisiones en una era en la existen diferentes opciones de tratamiento preservadoras del recto. El objetivo de este estudio de base poblacional fue determinar la precisión de la estadificación mediante RMN del cáncer de recto precoz en la práctica diaria, ya sea combinada o no con la ecografía endorectal ( endorectal ultrasound, ERUS). Métodos: Los pacientes con cáncer de recto en estadio cT1‐2 que se sometieron a resección local o resección total del mesorrecto ( total mesorectal excision, TME) sin (quimio) radioterapia neoadyuvante fueron seleccionados a partir del registro auditado ColoRectal holandés, entre el 1 de enero de 2011 y el 31 de diciembre de 2018. La precisión de las imágenes se expresó como sensibilidad, especificidad y valores predictivos positivo y negativo ( positive‐ and negative predicting value, PPV / NPV). Resultados: De un total de 7.382 pacientes registrados con cáncer de recto en estadio cT1‐2, se incluyeron 5.539 pacientes (5.288 solamente RMN, 251 RMN + ERUS; 1.059 cT1 y 4.480 cT2). Los pacientes pT1 fueron sobreestadificados cuando se utilizó únicamente la RMN en un 54, 7% de los casos (792/1.448) y cuando se combinó RMN y ERUS en un 31, 0% (36/116). La infraestadificación de pT2 ocurrió en un 8, 2% (197/2.388) y en un 27, 9% (31/111), respectivamente. La RMN utilizada como única prueba sobreestadificó los casos pN0 en el 17, 3% (570/3.303) y el VPP del estadio cN0 fue del 76, 3% (2.733/3.583). De los 834 pacientes con estadio pT1N0, potencialmente adecuado para la resección local, 253 pacientes (30, 3%) se clasificaron correctamente como cT1N0, y 484 (58, 8%) y 97 (11, 6%) pacientes se sobreestadificaron como cT2N0 y cT1‐2N1, respectivamente. Conclusión: Este estudio de base poblacional holandés en pacientes que se sometieron a una resección local o a cirugía TME por cáncer de recto cT1‐2 con estadificación preoperatoria mediante RMN, muestra una considerable sobreestadificación, lo que indica las debilidades y oportunidades en las estrategias de preservación del recto.